ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PRODUK SPRING BED PADA PT. MASSINDO SINAR PRATAMA - Taroreh, Eric Joseph; Tinangon, Jantje J.; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Determination of the cost of production is an important problem in a manufacturing company where the activity is to process the raw materials into finished materials subsequently sold to consumers for a profit. Cost of production is the cost of production which has applied to all finished products are being manufactured during a certain period. This study aims to determine the calculation of the cost of production at PT. Massindo Sinar Pratama. Analyses were performed using the descriptive method in qualitative to be a method to collect data, compiled, interpreted, and analyzed so as to provide an overview of the state of the subject and the object under study is based on facts. From these results it can be seen in the production process of spring, charging based on the type and size of production resulting in a period of one month. With the charge of direct materials, direct labor costs and factory overhead costs. Direct materials used include; Foam, Cloth spring, Spriral iron, wood, and plastic legs. The imposition of direct labor costs based on rates of production units produced. Imposition of factory overhead costs to products based on the overhead costs are determined upfront.